Laboratory astrophysical collisionless shock experiments on Omega and NIF. (March 2016) - Park, Hye-Sook; Ross, J. S.; Huntington, C. M.; Fiuza, F.; Ryutov, D.; Casey, D.; Drake, R. P.; Fiksel, G.; Froula, D.; Gregori, G.; Kugland, N. L.; Kuranz, C.; et al.
Abstract: We are performing scaled astrophysics experiments on Omega and on NIF. Laser driven counter-streaming interpenetrating supersonic plasma flows can be studied to understand astrophysical electromagnetic plasma phenomena in a controlled laboratory setting. In our Omega experiments, the counter-streaming flow plasma state is measured using Thomson scattering diagnostics, demonstrating the plasma flows are indeed super-sonic and in the collisionless regime. We observe a surprising additional electron and ion heating from ion drag force in the double flow experiments that are attributed to the ion drag force and electrostatic instabilities. [1] A proton probe is used to image the electric and magnetic fields. We observe unexpected large, stable and reproducible electromagnetic field structures that arise in the counter-streaming flows [2]. The Biermann battery magnetic field generated near the target plane, advected along the flows, and recompressed near the midplane explains the cause of such self-organizing field structures [3]. A D 3 He implosion proton probe image showed very clear filamentary structures; three-dimensional Particle-In-Cell simulations and simulated proton radiography images indicate that these filamentary structures are generated by Weibel instabilities and that the magnetization level (ratio of magnetic energy over kinetic energy in the system) is ∼0.01 [4]. These findings have very high astrophysical relevance and significant implications. We expect to observe true collisionless shock formation when we use >100 kJ laser energy on NIF.